Effect of Boron on Growth and Yield Parameters of Cauliflower (Brassica oleracea var botrytis cv Snow Mystique) in Terhathum, Nepal - Poudel, Nabin; Baral, Purnima; Neupane, Muna; Shrestha, Sundar Man; Shrestha, Arjun Kumar; Bhatta, Sandesh (International Journal of Applied Sciences and Biotechnology, 2022)
A study was conducted to determine the effect of different levels of boron on growth and yield parameters of Snow Mystique variety of cauliflower at farmer’s field in Myanglung, Terhathum, Nepal during the winter season of 2019 AD. Five levels of boron viz, control (0 kg/ha), 0.5 kg/ha, 1.0 kg/ha, 1.5 kg/ha, and 2.1 kg/ha were applied in the field that was laid out in Randomized Complete Block Design (RCBD) with four replications. Data were recorded regarding plant height, canopy cover, and leaf number at 30, 45, 60, and 75 days after transplanting while yield parameters like curd diameter, curd yield, and biological yield after harvest. Days to curd initiation, days to harvest, and incidence of hollowing were also recorded in this study. Results revealed that boron had significant effect on growth as well as yield parameters of cauliflower, where the value of these parameters were higher at higher boron dose. Boron at the rate of 2.1 kg/ha produced significantly higher curd yield (67.59 t/ha), curd diameter (25.21 cm) and biological yield (72.27 t/ha) whereas the value of these parameters were lowest with control. Similarly, boron had significant effect on incidence of hollowing where the application of boron at the rate of 2.1 kg/ha recorded the minimum incidence of hollowing (15.27 %). Results from this experiment concludes that application of boron at the rate of 2.1 kg/ha could be suggested for cauliflower growing farmers of Terhathum district for increased growth and yield of cauliflower. Int. J. Appl. Sci. Biotechnol. Vol 10(1): 41-49.